2017
DOI: 10.1007/s00431-017-3023-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in pediatric inpatients: a study based on a national mandatory reporting system

Abstract: MEs in hospitalized children occur in all medication processes and mainly involve dosing errors. Strategies should be developed to prevent MEs as these still threaten medication safety in pediatric inpatients. What is known: • Hospitalized children are more likely to experience medication errors than adults. • Voluntary national and local reporting and learning systems have previously been used to describe the nature and types of medication errors. What is new: • Medication errors in hospitalized children occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 27 publications
2
50
2
Order By: Relevance
“…In addition, the two studies showed similarities regarding modal characteristics where 'wrong dose' was the most common type of error. The substances that frequently occurred (paracetamol, gentamicin, ampicillin, morphine and cefuroxime) did correlate to the top-selling drugs in Denmark rather to the results in our study, but the three predominant drug classes were the same 24.…”
contrasting
confidence: 58%
“…In addition, the two studies showed similarities regarding modal characteristics where 'wrong dose' was the most common type of error. The substances that frequently occurred (paracetamol, gentamicin, ampicillin, morphine and cefuroxime) did correlate to the top-selling drugs in Denmark rather to the results in our study, but the three predominant drug classes were the same 24.…”
contrasting
confidence: 58%
“…[1][2] Hospitalized children, especially those treated in the intensive care units or under the age of 2 years may be particularly prone to MEs. [1][2][3][4] In order to improve medication safety, MEs and practices which potentially contribute to MEs must be explored. Different approaches, including incident reporting, chart review and observations have previously been used to detect MEs in paediatric hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have previously used assessment of actual or potential harm of MEs to identify those most relevant to prevent. [8][9][10] In this study, we aimed to identify MEs and potentially unsafe medication practices (PUMPs) involving practices or conditions with the opportunity to cause MEs in hospitalized children, and to assess the potential harm of these using raters of different professions.…”
Section: Introductionmentioning
confidence: 99%
“…PCA relies on the use of a program with different parameters such as bolus dose, lockout interval, hourly maximum dose and the drugs used, that will allow the patient to receive opioids in a predetermined pattern. Programming errors of the pump are therefore an important challenge concerning the safety of PCA ( 8 ). A recent retrospective study collecting the clinical records of 82,698 pediatric surgical patients demonstrated that 0.19% of cases experienced PCA device-related errors with the electronic programmable pump showing the highest error rate ( 6 ).…”
Section: The Silent Dangers Of Pca Use In Children and Adolescentsmentioning
confidence: 99%
“…A mean error rate of 4.12% (10 errors) was observed, and although it may seem lower than the 20% of PCA medication errors reported in the United States of America ( 22 ), it reflects 10 patients who would have received incorrect medication dosing ( 9 ). Medication errors can pose a serious problem to the pediatric patient population because medication dosing is weight or surface area based ( 8 ). Although PCA device-related errors may not be frequent, they may prompt to serious consequences such as prolonged hospitalization and disabilities.…”
Section: The Silent Dangers Of Pca Use In Children and Adolescentsmentioning
confidence: 99%